The association between intolerance of uncertainty and psychological burden among caregivers of children with autism and the impact on their quality of life - Mansoor, Khulood Mohammed Al (Frontiers in Psychiatry, 2025)
IntroductionCaregivers of children with Autism Spectrum Disorder (ASD) often face significant stressors, including financial strain, social stigma, emotional exhaustion, and unpredictable daily routines. These challenges can severely impact their quality of life (QoL). This study aimed to examine the relationship between intolerance of uncertainty, caregiver burden, and QoL among caregivers of children with autism.MethodsA cross-sectional study was conducted with 59 caregivers from six branches of the Obour Company for Human Development in Riyadh. Data were collected electronically using a sociodemographic data sheet, the Intolerance of Uncertainty Scale, the Zarit Burden Interview (short form), and the World Health Organization Quality of Life Scale (brief form).ResultsFindings revealed that two-thirds of caregivers experienced high to moderate levels of intolerance to uncertainty and a moderate burden, while 13.6% reported a high burden. Nearly 60% of participants reported low overall QoL, particularly in the psychological and social domains. A significant positive correlation was found between intolerance of uncertainty and caregiver burden. Additionally, significant negative associations were observed between QoL scores and both intolerance of uncertainty and caregiver burden, except in the environmental domain. Intolerance of uncertainty emerged as a significant inverse predictor of overall QoL.DiscussionThese results emphasize the psychological toll of caregiving for children with ASD. Interventions such as family- and community-based support programs and child behavioral training are essential to reduce caregiver burden and enhance QoL. Tailored services should be prioritized in clinical practice to support caregivers more effectively.